IGF2 stimulates fetal growth in a sex- and organ-dependent manner - White, Verónica (2018)
BackgroundInsulin-like growth factor 2 (IGF2) is a key determinant of fetal growth, and the altered expression of IGF2 is implicated in fetal growth disorders and maternal metabolic derangements including gestational diabetes. Here we studied how increased levels of IGF2 in late pregnancy affect fetal growth.MethodsWe employed a rat model of repeated intrafetal IGF2 administration in late pregnancy, i.e., during GD19-GD21, and measured the consequences on fetal organ weight and expression of insulin/IGF-axis components.ResultsIGF2 treatment tended to increase fetal weight, but only weight increase of the fetal stomach reached significance (+33±9%; P<0.01). Sex-dependent data analysis revealed a sexual dimorphism of IGF2 action. In male fetuses, IGF2 administration significantly increased fetal weight (+13±3%; P<0.05) and weight of fetal stomach (+42±10%; P<0.01), intestine (+26±5%; P<0.05), liver (+13±4%; P<0.05), and pancreas (+25±8%; P<0.05). Weights of heart, lungs, and kidneys were unchanged. In female fetuses, IGF2 increased only stomach weight (+26±9%; P<0.05). Furthermore, gene expression of insulin/IGF axis in the heart, lungs, liver, and stomach was more sensitive toward IGF2 treatment in male than in female fetuses.ConclusionData suggest that elevated circulating IGF2 in late pregnancy predominantly stimulates organ growth of the digestive system, and male fetuses are more susceptible toward the IGF2 effects than female fetuses.